Análisis de costos en el área de ginecología de la Clínica Avilés del cantón La Maná provincia de Cotopaxi periodo enero – julio 2013 - García Indio, Fanny Maricela (2013)
In the present investigation was developed an analysis of costs of providing services in the area of gynecology of Aviles Clinic period January to July 2013, in Chapter I information was compiled from different authors, that contributed to the development of research , Chapter II, the different techniques and research methods for the collection of statistical data through surveys of the accountant and accounting assistants and applied the manager interview clinic owner who contributed fundamentals needed to develop this study, in third Chapter....